DINAMIKA KESETARAAN GENDER DI ARAB SAUDI: SEBUAH HARAPAN BARU DI ERA RAJA SALMAN - Dewi, Nevy Rusmarina; Fikri, Azza Ihsanul; Febriani, Afifah (Faculty of Social and Political Sciences, Universitas Muhammadiyah Malang, 2020)
Saudi Arabia is one of the Moslem countries in the Middle East which limits women?s rights. These women have limited access to economy, education, as well as politics. 2009 was the milestone for women?s public participation in Saudi Arabia. This research aims to analyze the development of gender equality issue in Saudi Arabia which encourages policy changes in the era of King Salman. Gender is a character owned by someone in accordance with his/her social role based on his/her sex. Gender equality focuses on the equality of social role which is obtained by both men and women. In Koran surah Al- Baqarah article 288, there are two perspectives about women?s position which included normative and contextual aspects. Gender equality in Islamic?s perspective has been recognized in OKI?s Charter article 6. This research uses qualitative method with literature study approach. The result shows that the dynamic of policy changes in Saudi Arabia is influenced by the condition of Saudi?s women socio-cultural itself, the debate of the Ulama about gender equality which proposes Wassatiya?s perspective and Vision 2030 by Mohammad bin Salman as the hope of the implementation of the policy which gives a bigger opportunity for women?s role in public.